CORRELAÇÃO ENTRE QUALIDADE DE VIDA NO TRABALHO E CLIMA ORGANIZACIONAL: O CASO DA PRÓ-REITORIA DE GRADUAÇÃO DE UMA UNIVERSIDADE PÚBLICA - Sales, Thamires Vettorazzi de Moura (2020)
Introduction: With the evolution of society, human capital has become for organizations a relevant factor to organizational development, It´s making the areas of people management and organizational behavior have become an object of growing social interes